Mind the Plateau: A Mathematical Modeling Analysis of Long-Term GLP-1 Receptor Agonist Treatment - Patrice A. Hubert; Christopher Coleman; Gregory J. Grosicki; Jessica Kiel; Madelyn Shepherd; Holly F. Lofton; Steven B. Heymsfield; J. Graham Thomas; Nikhil V. Dhurandhar; Satya S. Jonnalagadda (Journal of the Academy of Nutrition and Dietetics, 2026)

Towards an enhanced role for human biomonitoring in REACH regulation: Current landscape and future prospects - Susana Viegas; Tiina Santonen; Michael Bader; Nancy B. Hopf; Robert Pasanen-Kase; Kate Jones; Karen S. Galea; Steven Verpaele; Adrian Tristram; Ovnair Sepai; Natalie von Goetz; Paul T.J. Scheepers; et al. (Regulatory Toxicology and Pharmacology, 2026)

Far ultraviolet carbon emissions in the Mars aurora: Brightness, intensity ratios and seasonal dependence - J.C. Gérard; L. Soret; B. Hubert; R. Lillis; S. Jain; J. Deighan (Icarus, 2026)

Experimental assessment of ambient gamma dose equivalent rates measured outdoors in the Republic of Benin from 2019 to 2020 - Arnaud A. Gbetchedji; Daniel S. Takou; N. Innocent Gbaï; Mahougnon B. Zinsou; Hubert C. Hounsossou; Thierry C. M. Medehouenou; Rodrigue S. Allodji (Environmental Monitoring and Assessment, 2026)

Eemian climate seasonality reconstructed from intra-tooth oxygen, carbon, and nitrogen stable isotopes in equid enamel from Neumark-Nord 2, Germany - Marissa Vink; Jennifer N. Leichliter; Daniel R. Green; Sven Brömme; Théo Tacail; Lutz Kindler; Wil Roebroeks; Sabine Gaudzinski-Windheuser; Gerald H. Haug; Hubert B. Vonhof; Alfredo Martínez-García; Thomas Tütken; et al. (Quaternary Science Reviews, 2026)

Planktic foraminifera response to the early Eocene Climatic Optimum in the southern high-latitude Indian Ocean (ODP Site 738) - Masoumeh Gheiasvand; Brian T. Huber; Hubert B. Vonhof; Denis Fiorillo; Annachiara Bartolini (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Analysis of cosmic ray-induced neutron spectra recorded during PIRATA oceanographic cruises - G. Hubert; G. Herbert; A. Tilhac; R. Rey; B. Bourlès (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Preaccretionary origin of clay minerals in CI chondritic objects? Insights from the Orgueil clay mineralogy and iron oxidation state - J.-C. Viennet; K. Amano; L. Delbes; B. Lavina; F. Hubert; S. Bernard; S. Yaroslavtsev; D. Bessas; A. Chumakov; J.-P. Celse; M. Gounelle; L. Remusat; et al. (Earth and Planetary Science Letters, 2025)

The Martian oxygen green line dayglow: response to solar activity - L. Soret; H. Robin; J.-C. Gérard; L. Gkouvelis; I. Thomas; B. Ristic; Y. Willame; B. Hubert; A.C. Vandaele; J.P. Mason; F. Daerden; M.R. Patel (Icarus, 2025)

Diachronic reconstruction of palaeoclimates and diet through stable isotopes (δ13C and δ18O) and 2D geometric morphometrics from cave bear (Ursus spelaeus) dentition - Daniel Charters; Hubert B. Vonhof; Richard P. Brown; Dominique Bonjean; Isabelle De Groote; Carolin Pellio; Grégory Abrams; Carlo Meloro (Quaternary International, 2025)

Inversion of ultraviolet occultation profiles in a dusty atmosphere: Analytic and numerical methods - B. Hubert; L. Soret; J.-C. Gérard; G. Wautelet; G. Munhoven; A. Piccialli; A.-C. Vandaele (Icarus, 2025)

Plant and algal lipidomes: Analysis, composition, and their societal significance - Juliette Jouhet; Eliana Alves; Yohann Boutté; Sylvain Darnet; Frédéric Domergue; Thierry Durand; Pauline Fischer; Laetitia Fouillen; Mara Grube; Jérôme Joubès; Uldis Kalnenieks; Joanna M. Kargul; et al. (Progress in Lipid Research, 2024)

Comparing open-source DEM frameworks for simulations of common bulk processes - M. Dosta; D. Andre; V. Angelidakis; R.A. Caulk; M.A. Celigueta; B. Chareyre; J.-F. Dietiker; J. Girardot; N. Govender; C. Hubert; R. Kobyłka; A.F. Moura; et al. (Computer Physics Communications, 2024)

Mixta mediterraneensis as a novel and abundant gut symbiont of the allergen-producing domestic mite Blomia tropicalis - Tomas Erban; Bruno Sopko; Pavel B. Klimov; Jan Hubert (Experimental and Applied Acarology, 2024)
Blomia tropicalis is an allergen-producing mite in the human environment in tropical regions. The microbiome of B. tropicalis was described using the barcode sequencing region of V4 16S rDNA and genome assemblage. Mixta mediterraneensis , previously isolated from human skin swabs, was identified as a B. tropicalis gut symbiont based on genome assembly. The microbiome contains two bacteria, Staphylococcus and M. mediterraneensis . The number of M. mediterraneensis 16S DNA copies was 10 6 per mite and 10 9 per feces in the rearing chamber based on qPCR quantification. The profile of this bacterium reached 50% of reads in the mite gut and feces. Genomic analyses revealed that the bacterium has several metabolic pathways that suggest metabolic cooperation with the mite host in vitamin and amino acid synthesis, nitrogen recycling, and antimicrobial defense. Lysozyme is present in the symbiotic bacterium but absent in the mite. The B. tropicalis microbiome contained Staphylococcus , which accelerates mite population growth. Mites can digest Staphylococcus by using specific enzymes with hydrolytic functions against bacterial cell walls (chitinases and cathepsin D), leading to endocytosis of bacteria and their degradation in lysosomes and phagosomes. Gene expression analysis of B. tropicalis indicated that phagocytosis was mediated by the PI3-kinase/Akt pathway interacting with the invasins produced by M. mediterraneensis . Moreover, the symbiont had metabolic pathways that allowed it to recycle the mite metabolic waste product guanine, known as a mite attractant. The mite host symbiont enhances mite aggregation in the feces, and the fecal–oral transmission route is excepted.

Coral carbonate-bound isotopes reveal monsoonal influence on nitrogen sources in Southeastern China's Greater Bay Area from the mid-Holocene until the Anthropocene - Jonathan D. Cybulski; Nicolas N. Duprey; Benoit Thibodeau; Moriaki Yasuhara; Naomi Geeraert; Nicole Leonard; Hubert B. Vonhof; Alfredo Martínez-García; David M. Baker (Marine Pollution Bulletin, 2023)

The brightness of the CO Cameron bands in the martian discrete aurora: A study based on revised cross sections - J.-C. Gérard; L. Soret; B. Hubert; L. Neary; F. Daerden (Icarus, 2023)

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Revised age and stratigraphy of the classic Homo erectus-bearing succession at Trinil (Java, Indonesia) - Sander L. Hilgen; Eduard Pop; Shinatria Adhityatama; Tom A. Veldkamp; Harold W.K. Berghuis; Indra Sutisna; Dida Yurnaldi; Guillaume Dupont-Nivet; Tony Reimann; Norbert Nowaczyk; Klaudia F. Kuiper; Wout Krijgsman; et al. (Quaternary Science Reviews, 2023)

Population growth and respiration in the dust mite Dermatophagoides farinae under different temperature and humidity regimes - Tereza Vackova; Stano Pekar; Pavel B. Klimov; Jan Hubert (Experimental and Applied Acarology, 2023)

Using point-of-view cameras (Crittercams) to document potential risk behaviors for Guinea worm (Dracunculus medinensis) transmission in domestic cats in Chad, Africa - Ellen Haynes; Kayla B. Garrett; Erin K. Box; Hubert Zirimwabagabo; Philip Tchindebet Oaukou; Kyler Abernathy; Michael J. Yabsley; Christopher A. Cleveland (Applied Animal Behaviour Science, 2023)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Sharing a bed with mites: preferences of the house dust mite Dermatophagoides farinae in a temperature gradient - Tereza Vackova; Stano Pekar; Pavel B. Klimov; Jan Hubert (Experimental and Applied Acarology, 2021)

High intensity aerobic exercise improves information processing and motor performance in individuals with Parkinson’s disease - Anson B. Rosenfeldt; Mandy Miller Koop; Hubert H. Fernandez; Jay L. Alberts (Experimental Brain Research, 2021)

Sensitive quantification of dipicolinic acid from bacterial endospores in soils and sediments - Jayne E. Rattray; Anirban Chakraborty; Carmen Li; Gretta Elizondo; Nisha John; Michelle Wong; Jagoš R. Radović; Thomas B. P. Oldenburg; Casey R. J. Hubert (Environmental Microbiology, 2021)
Summary Endospore‐forming bacteria make up an important and numerically significant component of microbial communities in a range of settings including soils, industry, hospitals and marine sediments extending into the deep subsurface. Bacterial endospores are non‐reproductive structures that protect DNA and improve cell survival during periods unfavourable for bacterial growth. An important determinant of endospores withstanding extreme environmental conditions is 2,6‐pyridine dicarboxylic acid (i.e. dipicolinic acid, or DPA), which contributes heat resistance. This study presents an improved HPLC‐fluorescence method for DPA quantification using a single 10‐min run with pre‐column Tb 3+ chelation. Relative to existing DPA quantification methods, specific improvements pertain to sensitivity, detection limit and range, as well as the development of new free DPA and spore‐specific DPA proxies. The method distinguishes DPA from intact and recently germinated spores, enabling responses to germinants in natural samples or experiments to be assessed in a new way. DPA‐based endospore quantification depends on accurate spore‐specific DPA contents, in particular, thermophilic spores are shown to have a higher DPA content, meaning that marine sediments with plentiful thermophilic spores may require spore number estimates to be revisited. This method has a wide range of potential applications for more accurately quantifying bacterial endospores in diverse environmental samples.

Anaerobic microbial communities and their potential for bioenergy production in heavily biodegraded petroleum reservoirs - Júlia R. de Rezende; Thomas B. P. Oldenburg; Tetyana Korin; William D. L. Richardson; Milovan Fustic; Carolyn M. Aitken; Bernard F. J. Bowler; Angela Sherry; Alexander Grigoryan; Gerrit Voordouw; Stephen R. Larter; Ian M. Head; et al. (Environmental Microbiology, 2020)
Summary Most of the oil in low temperature, non‐uplifted reservoirs is biodegraded due to millions of years of microbial activity, including via methanogenesis from crude oil. To evaluate stimulating additional methanogenesis in already heavily biodegraded oil reservoirs, oil sands samples were amended with nutrients and electron acceptors, but oil sands bitumen was the only organic substrate. Methane production was monitored for over 3000 days. Methanogenesis was observed in duplicate microcosms that were unamended, amended with sulfate or that were initially oxic, however methanogenesis was not observed in nitrate‐amended controls. The highest rate of methane production was 0.15 μmol CH 4 g −1 oil d −1 , orders of magnitude lower than other reports of methanogenesis from lighter crude oils. Methanogenic Archaea and several potential syntrophic bacterial partners were detected following the incubations. GC–MS and FTICR–MS revealed no significant bitumen alteration for any specific compound or compound class, suggesting that the very slow methanogenesis observed was coupled to bitumen biodegradation in an unspecific manner. After 3000 days, methanogenic communities were amended with benzoate resulting in methanogenesis rates that were 110‐fold greater. This suggests that oil‐to‐methane conversion is limited by the recalcitrant nature of oil sands bitumen, not the microbial communities resident in heavy oil reservoirs.

Megacity development and the demise of coastal coral communities: Evidence from coral skeleton δ 15 N records in the Pearl River estuary - Nicolas N. Duprey; Tony X. Wang; Taihun Kim; Jonathan D. Cybulski; Hubert B. Vonhof; Paul J. Crutzen; Gerald H. Haug; Daniel M. Sigman; Alfredo Martínez‐García; David M. Baker (Global Change Biology, 2020)
Historical coral skeleton (CS) δ 18 O and δ 15 N records were produced from samples recovered from sedimentary deposits, held in natural history museum collections, and cored into modern coral heads. These records were used to assess the influence of global warming and regional eutrophication, respectively, on the decline of coastal coral communities following the development of the Pearl River Delta (PRD) megacity, China. We find that, until 2007, ocean warming was not a major threat to coral communities in the Pearl River estuary; instead, nitrogen (N) inputs dominated impacts. The high but stable CS‐δ 15 N values (9‰–12‰ vs. air) observed from the mid‐Holocene until 1980 indicate that soil and stream denitrification reduced and modulated the hydrologic inputs of N, blunting the rise in coastal N sources during the early phase of the Pearl River estuary urbanization. However, an unprecedented CS‐δ 15 N peak was observed from 1987 to 1993 (>13‰ vs. air), concomitant to an increase of NH 4 + concentration, consistent with the rapid Pearl River estuary urbanization as the main cause for this eutrophication event. We suggest that widespread discharge of domestic sewage entered directly into the estuary, preventing removal by natural denitrification hotspots. We argue that this event caused the dramatic decline of the Pearl River estuary coral communities reported from 1980 to 2000. Subsequently, the coral record shows that the implementation of improved wastewater management policies succeeded in bringing down both CS‐δ 15 N and NH 4 + concentrations in the early 2000s. This study points to the potential importance of eutrophication over ocean warming in coral decline along urbanized coastlines and in particular in the vicinity of megacities.

Fluid evolution and ore deposition in the Harz Mountains revisited: isotope and crush-leach analyses of fluid inclusions - Stefan de Graaf; Volker Lüders; David A. Banks; Marta Sośnicka; John J. G. Reijmer; Heike Kaden; Hubert B. Vonhof (Mineralium Deposita, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Going Beyond Standard Ocean Color Observations: Lidar and Polarimetry - Cédric Jamet; Amir Ibrahim; Ziauddin Ahmad; Federico Angelini; Marcel Babin; Michael J. Behrenfeld; Emmanuel Boss; Brian Cairns; James Churnside; Jacek Chowdhary; Anthony B. Davis; Davide Dionisi; et al. (Frontiers in Marine Science, 2019)

Chilling and forcing temperatures interact to predict the onset of wood formation in Northern Hemisphere conifers - Nicolas Delpierre; Ségolène Lireux; Florian Hartig; Jesus Julio Camarero; Alissar Cheaib; Katarina Čufar; Henri Cuny; Annie Deslauriers; Patrick Fonti; Jožica Gričar; Jian‐Guo Huang; Cornelia Krause; et al. (Global Change Biology, 2019)
The phenology of wood formation is a critical process to consider for predicting how trees from the temperate and boreal zones may react to climate change. Compared to leaf phenology, however, the determinism of wood phenology is still poorly known. Here, we compared for the first time three alternative ecophysiological model classes ( threshold models, heat‐sum models and chilling‐influenced heat‐sum models) and an empirical model in their ability to predict the starting date of xylem cell enlargement in spring, for four major Northern Hemisphere conifers ( Larix decidua, Pinus sylvestris , Picea abies and Picea mariana ). We fitted models with Bayesian inference to wood phenological data collected for 220 site‐years over Europe and Canada. The chilling‐influenced heat‐sum model received most support for all the four studied species, predicting validation data with a 7.7‐day error, which is within one day of the observed data resolution. We conclude that both chilling and forcing temperatures determine the onset of wood formation in Northern Hemisphere conifers. Importantly, the chilling‐influenced heat‐sum model showed virtually no spatial bias whichever the species, despite the large environmental gradients considered. This suggests that the spring onset of wood formation is far less affected by local adaptation than by environmentally driven plasticity. In a context of climate change, we therefore expect rising winter–spring temperature to exert ambivalent effects on the spring onset of wood formation, tending to hasten it through the accumulation of forcing temperature, but imposing a higher forcing temperature requirement through the lower accumulation of chilling.

Livestock productivity as indicator of vulnerability to climate hazards: a Mongolian case study - F. Joly; R. Sabatier; B. Hubert; B. Munkhtuya (Natural Hazards, 2018)

A primer on systematic reviews in toxicology - Sebastian Hoffmann; Rob B. M. de Vries; Martin L. Stephens; Nancy B. Beck; Hubert A. A. M. Dirven; John R. Fowle; Julie E. Goodman; Thomas Hartung; Ian Kimber; Manoj M. Lalu; Kristina Thayer; Paul Whaley; et al. (Archives of Toxicology, 2017)

Progressive Plant Extension Applied to the Soil Treatment Facility of the “Arge Ground Unit”, Particularly Enhancement of the Treatment Range and Optimization of the Product Flows: An Example for Successful Urban Mining - Günter Hirsch; Hubert Rammer; Rüdiger B. Richter; Helmut Flachberger; Reagan Kabogozza (BHM Berg- und Hüttenmännische Monatshefte, 2016)

“Panta Rhei—Everything Flows”: Change in hydrology and society—The IAHS Scientific Decade 2013–2022 - A. Montanari; G. Young; H.H.G. Savenije; D. Hughes; T. Wagener; L.L. Ren; D. Koutsoyiannis; C. Cudennec; E. Toth; S. Grimaldi; G. Blöschl; M. Sivapalan; et al. (Hydrological Sciences Journal, 2013)

Massive dominance of Epsilonproteobacteria in formation waters from a Canadian oil sands reservoir containing severely biodegraded oil - Casey R. J. Hubert; Thomas B. P. Oldenburg; Milovan Fustic; Neil D. Gray; Stephen R. Larter; Kevin Penn; Arlene K. Rowan; Rekha Seshadri; Angela Sherry; Richard Swainsbury; Gerrit Voordouw; Johanna K. Voordouw; et al. (Environmental Microbiology, 2012)
Summary The subsurface microbiology of an Athabasca oil sands reservoir in western Canada containing severely biodegraded oil was investigated by combining 16S rRNA gene‐ and polar lipid‐based analyses of reservoir formation water with geochemical analyses of the crude oil and formation water. Biomass was filtered from formation water, DNA was extracted using two different methods, and 16S rRNA gene fragments were amplified with several different primer pairs prior to cloning and sequencing or community fingerprinting by denaturing gradient gel electrophoresis (DGGE). Similar results were obtained irrespective of the DNA extraction method or primers used. Archaeal libraries were dominated by Methanomicrobiales (410 of 414 total sequences formed a dominant phylotype affiliated with a Methanoregula sp.), consistent with the proposed dominant role of CO 2 ‐reducing methanogens in crude oil biodegradation. In two bacterial 16S rRNA clone libraries generated with different primer pairs, > 99% and 100% of the sequences were affiliated with Epsilonproteobacteria ( n = 382 and 72 total clones respectively). This massive dominance of Epsilonproteobacteria sequences was again obtained in a third library (99% of sequences; n = 96 clones) using a third universal bacterial primer pair (inosine‐341f and 1492r). Sequencing of bands from DGGE profiles and intact polar lipid analyses were in accordance with the bacterial clone library results. Epsilonproteobacterial OTUs were affiliated with Sulfuricurvum , Arcobacter and Sulfurospirillum spp. detected in other oil field habitats. The dominant organism revealed by the bacterial libraries (87% of all sequences) is a close relative of Sulfuricurvum kujiense – an organism capable of oxidizing reduced sulfur compounds in crude oil. Geochemical analysis of organic extracts from bitumen at different reservoir depths down to the oil water transition zone of these oil sands indicated active biodegradation of dibenzothiophenes, and stable sulfur isotope ratios for elemental sulfur and sulfate in formation waters were indicative of anaerobic oxidation of sulfur compounds. Microbial desulfurization of crude oil may be an important metabolism for Epsilonproteobacteria indigenous to oil reservoirs with elevated sulfur content and may explain their prevalence in formation waters from highly biodegraded petroleum systems.

Can shells of freshwater mussels (Unionidae) be used to estimate low summer discharge of rivers and associated droughts? - Emma A. A. Versteegh; Hubert B. Vonhof; Simon R. Troelstra; Dick Kroon (International Journal of Earth Sciences, 2011)

Dose finding of melatonin for chronic idiopathic childhood sleep onset insomnia: an RCT - Ingeborg M. van Geijlswijk; Kristiaan B. van der Heijden; A. C. G. Egberts; Hubert P. L. M. Korzilius; Marcel G. Smits (Psychopharmacology, 2010)

Molecular biodiversity and population structure in common ash (Fraxinus excelsior L.) in Britain: implications for conservation - B. G. SUTHERLAND; A. BELAJ; S. NIER; J. E. COTTRELL; S. P VAUGHAN; J. HUBERT; K. RUSSELL (Molecular Ecology, 2010)

Records of large earthquakes in lake sediments along the North Anatolian Fault, Turkey - X. Boës; S. B. Moran; J. King; M. N. Cağatay; A. Hubert-Ferrari (Journal of Paleolimnology, 2010)

Movements by adult cutthroat trout in a lotic system: implications for watershed‐scale management - T. B. SANDERSON; W. A. HUBERT (Fisheries Management and Ecology, 2009)
Movements by adult cutthroat trout, Oncorhynchus clarkii (Richardson), were assessed from autumn to summer in the Salt River watershed, Wyoming‐Idaho, USA by radio telemetry. Adult cutthroat trout were captured during September and October 2005 in the main stem of the Salt River, surgically implanted with radio transmitters, and tracked through to August 2006. Adult cutthroat trout were relatively sedentary and resided primarily in pools from October to March, but their movement rates increased during April. Higher movement rates were observed among tagged fish during May and early June. Among 43 fish residing in the Salt River during April 2006, 44% remained in the river, 37% moved into mountain tributaries and 19% moved into spring streams during the spawning season. Fish did not use segments of mountain tributaries or the upstream Salt River where fish passage was blocked by anthropogenic barriers or the channel was dewatered during summer. Almost all the fish that moved into spring streams used spring streams where pools and gravel–cobble riffles had been constructed by landowners. The results suggest that adult Snake River cutthroat move widely during May and early June to use spawning habitat in mountain tributaries and improved spring streams. Maintaining the ability of adult fish to move into mountain streams with spawning habitat, preserving spawning habitat in accessible mountain tributaries and removing barriers to upstream movements, and re‐establishing summer stream flows in mountain tributaries affected by dams appear to be habitat management alternatives to preserve the Snake River cutthroat trout fishery in the Salt River.

Morphology–diet relationships in four killifishes (Teleostei, Cyprinodontidae, Orestias ) from Lake Titicaca - E. Maldonado; N. Hubert; P. Sagnes; B. De MÉrona (Journal of Fish Biology, 2009)
This study explores the relationship between morphology and diet in four Andean killifishes ( Orestias ) from Lake Titicaca that are known to differ in habitat use. Species that fed preferentially on amphipods ( Orestias albus ) or molluscs ( Orestias luteus ) separated in multivariate space from other species that feed on cladocera and algae ( Orestias agassii and Orestias jussiei ). Generally, specimens feeding on cladocera were characterized by a short, blunt nose with a small mouth; whereas, specimens feeding on amphipods exhibited a long snout with a large mouth. Specimens including molluscs in their diet tended to have a larger posterior part of the head and the larger opercles than others; while the occurrence of substratum in gut content was generally related to a short but deep head. The present analysis suggests that the littoral O. jussiei has an intermediate phenotype and diet between the pelagic ( O. agassii ) and benthic ( O. albus and O. luteus ) species. Results suggest that resource partitioning was occurring and that several morphological traits relate to characteristics of the diet, and it is inferred that the benthic, the pelagic and the littoral zones in the lake host different prey communities constituting distinct adaptive landscapes.

Somatolactin mRNA expression during the parr–smolt transformation in hatchery‐reared Atlantic salmon Salmo salar smolts - A. M. O’Keeffe; S. Hubert; M. Voisin; B. Houeix; D. Cotter; M. T. Cairns (Journal of Fish Biology, 2008)
Expression of somatolactin (SL) mRNA was quantified during smoltification at 2 week intervals during January and February and weekly during March, April and May 2004 in a line‐bred ranching stock of Atlantic salmon Salmo salar . Gene expression of SL (and a splice variant termed SL 180 ) was lower in fish sampled in the later weeks of smoltification than in those at the beginning, a pattern opposite to that of gill Na + K + ‐ATPase activity.

Interactions Between Euphorbia esula Toxins and Bovine Ruminal Microbes - Scott L. Kronberg; Fathi T. Halaweish; Mindy B. Hubert; Paul J. Weimer (Journal of Chemical Ecology, 2006)

Cocaine- and amphetamine-regulated transcript peptides play a role in drug abuse and are potential therapeutic targets - Michael J. Kuhar; Jason N. Jaworski; George W. Hubert; Kelly B. Philpot; Geraldina Dominguez (The AAPS Journal, 2005)

No increased risk of non-Hodgkin's lymphoma with steroids, estrogens and psychotropics (Netherlands) - Annette B. Beiderbeck; Elizabeth A. Holly; Miriam C.J.M. Sturkenboom; Jan W. Coebergh; Bruno H.Ch. Stricker; Hubert G.M. Leufkens (Cancer Causes & Control, 2003)

Toxic and Aversive Diterpenes of Euphorbia esula - Fathi T. Halaweish; Scott Kronberg; Mindy B. Hubert; James A. Rice (Journal of Chemical Ecology, 2002)

Brassinosteroids, microtubules and cell elongation in Arabidopsis thaliana . I. Molecular, cellular and physiological characterization of the Arabidopsis bul1 mutant, defective in the ? 7 -sterol-C5-desaturation step leading to brassinosteroid biosynthesis - Manuella Catterou; Frdric Dubois; Hubert Schaller; Laurent Aubanelle; Bat Vilcot; Brigitte S. Sangwan-Norreel; Rajbir S. Sangwan (Planta, 2001)

Abstracts - Gregor Anderluh; Ariana Barlič; Zdravko Podlesek; Gianfranco Menestrina; Peter Maček; Franc Gubenšek; Alioša Bavec; Blaž Cigiš; Matjaž Zorko; Alenka Čopič; Nataša Vučemilo; Igor Križaj; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

The structure of the human NDUFV1 gene encoding the 51-kDa subunit of mitochondrial complex I 61, A305, 1997.--> - René F.M. de Coo *, , Paul A.L. B; Hubert J.M. Smeets; Bernard A. van Oost (Mammalian Genome, 1999)

Detection of RET proto-oncogene codon 634 mutations using mass spectrometry - D. P. Little; A. Braun; B. Darnhofer-Demar; Andrea Frilling; Yunzhi Li; Robert T. McIver Jr.; Hubert Köster (Journal of Molecular Medicine, 1997)

Six new photolabile linkers for solid-phase synthesis. 1. Methods of preparation - Eva B. Åkerblom; Alf S. Nygren; K. Hubert Agback (Molecular Diversity, 1997)

Conservation of S-locus for self-incompatibility in Brassica napus (L.) and Brassica oleracea (L.) - W. Y. Cheung; G. Champagne; N. Hubert; L. Tulsieram; D. Charne; J. Patel; B. S. Landry (Theoretical and Applied Genetics, 1997)

Comparison of the genetic maps of Brassica napus and Brassica oleracea - W. Y. Cheung; G. Champagne; N. Hubert; B. S. Landry (Theoretical and Applied Genetics, 1997)